HAPSTR1 localizes HUWE1 to the nucleus to limit stress signaling pathways - Julie K. Monda; Xuezhen Ge; Moritz Hunkeler; Katherine A. Donovan; Michelle W. Ma; Cyrus Y. Jin; Marilyn Leonard; Eric S. Fischer; Eric J. Bennett (Cell Reports, 2023)
Summary: HUWE1 is a large, enigmatic HECT-domain ubiquitin ligase implicated in the regulation of diverse pathways, including DNA repair, apoptosis, and differentiation. How HUWE1 engages its structurally diverse substrates and how HUWE1 activity is regulated are unknown. Using unbiased quantitative proteomics, we find that HUWE1 targets substrates in a largely cell-type-specific manner. However, we identify C16orf72/HAPSTR1 as a robust HUWE1 substrate in multiple cell lines. Previously established physical and genetic interactions between HUWE1 and HAPSTR1 suggest that HAPSTR1 positively regulates HUWE1 function. Here, we show that HAPSTR1 is required for HUWE1 nuclear localization and nuclear substrate targeting. Nuclear HUWE1 is required for both cell proliferation and modulation of stress signaling pathways, including p53 and nuclear factor κB (NF-κB)-mediated signaling. Combined, our results define a role for HAPSTR1 in gating critical nuclear HUWE1 functions.